Prolongation of incubation time improves clinical diagnosis of Mycobacterium xenopi infection and allows susceptibility testing of mycobacterial strains against multiple antibiotics. (September 2020) - Cento, Valeria; Nava, Alice; Lepera, Valentina; Torri, Stefania; Colagrossi, Luna; Fanti, Diana; Vismara, Chiara; Perno, Carlo Federico; Mazzola, Ester
Highlights: Mycobacterium xenopi proved to be the slowest growing of all mycobacterial species analysed. A prolonged incubation time improves M. xenopi recovery and disease diagnosis. M. xenopi was fully susceptible in vitro to all of the most commonly used antibiotics. Abstract: Objectives: Mycobacterium xenopi is a nontuberculous mycobacterium (NTM) whose clinical diagnosis and drug susceptibility studies are frequently hampered by poor in vitro growth. Extending the culture incubation time from 42 days (common-standard) to 56 days could improve the likelihood of diagnosis and provide strains for phenotypic drug susceptibility profiling of this poorly studied but clinically relevant mycobacterium. Methods: Time-to-positivity of mycobacterial cultures incubated for 56 days were analysed and compared. Clinical mycobacteriosis was defined by ATS/IDSA criteria. In vitro susceptibility of M. xenopi isolates was tested by broth microdilution. Results: Of 3852 mycobacteria-positive cultures (26 different mycobacterial species), M. xenopi required by far the longest growth time in culture, exceeding the 42 days commonly used in routine diagnostics in 41.2% of cases versus 4.7% for other NTM and 2.0% for Mycobacterium tuberculosis complex ( P < 0.001). Prolonging the incubation time to 56 days had a great impact on M. xenopi diagnosis, as 56.3% (27/48) of patients would have not fulfilled the ATS/IDSA criteria at an incubation limited to 42 days. All 40 M. xenopi isolates from patients with clinical mycobacteriosis were fully susceptibility to macrolides and rifamycins in vitro and to moxifloxacin, amikacin and linezolid. Conclusion: These results indicate that a significant percentage (56.3%) of positive culture for M. xenopi would have incorrectly been reported as negative to clinicians without prolonging the incubation time to 56 days. Moreover, 56.3% of patients with M. xenopi disease would have missed the diagnosis along with an appropriate germ-based antimycobacterial treatment, otherwise fully effective.